(untitled) (Bangladesh Journal of Medical Microbiology, 2025)
Background: Pulmonary Aspergillosis has shown a significant rise in recent years, so its early diagnosis and laboratory detection is essential. Phenotypic methods such as, microscopy and culture remain widespread and essential tools for diagnosis of Aspergillus infection. Objective: The objective of the study was to compare phenotypic methods, such as microscopy and culture for detection of Aspergillus species from sputum samples of clinically suspected pulmonary tuberculosis cases. Methodology: A cross-sectional study was conducted from January 2021 to December 2021 in the Department of Microbiology of Sir Salimullah Medical College, Dhaka. A total of 176 sputum samples were collected from clinically suspected pulmonary tuberculosis patients. Mycobacterium tuberculosis was detected by Gene Xpert from the sputum sample. Aspergillus was identified by KOH mount microscopy and culture on Sabouraud’s chloramphenicol agar media with gentamicin. Species identification of Aspergillus was done by colony characteristics and lactophenol cotton blue staining using direct microscopy. Results: In this study, out of 176 sputum samples, Mycobacterium tuberculosis was detected by Gene Xpert in 28(15.91%) sputum samples. 24(13.64%) Aspergillus species were detected by culture and 20(11.36%) were detected by microscopy. Aspergillus fumigatus 12(50%) was the commonest isolated species, followed by Aspergillus niger 7(29.17%). Conclusion: Morphological identification systems, such as traditional culture methods and direct microscopic examination, have been always played a dominant role in Aspergillus identification. Bangladesh Journal of Medical Microbiology, July 2024;18(2):69-74